Genome analysis reveals evolutionary mechanisms of adaptation in systemic dimorphic fungi (2018)
Dimorphic fungal pathogens cause a significant human disease burden and unlike most fungal pathogens affect immunocompetent hosts. To examine the origin of virulence of these fungal pathogens, we compared genomes of classic systemic, opportunistic, and non-pathogenic species, including Emmonsia and two basal branching, non-pathogenic species in the Ajellomycetaceae, Helicocarpus griseus and Polytolypa hystricis. We found that gene families related to plant degradation, secondary metabolites synthesis, and amino acid and lipid metabolism are retained in H. griseus and P. hystricis. While genes involved in the virulence of dimorphic pathogenic fungi are conserved in saprophytes, changes in the copy number of proteases, kinases and transcription factors in systemic dimorphic relative to non-dimorphic species may have aided the evolution of specialized gene regulatory programs to rapidly adapt to higher temperatures and new nutritional environments. Notably, both of the basal branching, non-pathogenic species appear homothallic, with both mating type locus idiomorphs fused at a single locus, whereas all related pathogenic species are heterothallic. These differences revealed that independent changes in nutrient acquisition capacity have occurred in the Onygenaceae and Ajellomycetaceae, and underlie how the dimorphic pathogens have adapted to the human host and decreased their capacity for growth in environmental niches. © 2018 The Author(s).